2015
DOI: 10.1111/jne.12261
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Changes in Lactotrophs and Folliculo‐Stellate Cells in the Ovine Pituitary during the Annual Reproductive Cycle

Abstract: In seasonal mammals living in temperate zones, photoperiod regulates prolactin secretion, such that prolactin plasma concentrations peak during the summer months and are lowest during the winter. In sheep, a short-day breeder, circulating prolactin has important modulatory effects on the reproductive system via inhibitory actions on pituitary gonadotrophs and hypothalamic gonadotrophin-releasing hormone release. The exact cellular mechanisms that account for the chronic hypersecretion of prolactin during the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 40 publications
0
15
0
1
Order By: Relevance
“…Furthermore, gap junction inhibition using alpha glycyrrhetinic acid reduces dye coupling and prevents the network from displaying lactating-like wiring patterns during demand, most likely due to blockade of long-range signal entrainment [65]. Similarly, recent electron microscopy studies in the ovine pituitary have shown that lactotroph-lactotroph junctional contacts increase in line with the circannual peak of PRL during the nonbreeding season [84]. Therefore, episodes of structural and functional plasticity within the lactotroph population/network …”
Section: Lactotrophsmentioning
confidence: 93%
“…Furthermore, gap junction inhibition using alpha glycyrrhetinic acid reduces dye coupling and prevents the network from displaying lactating-like wiring patterns during demand, most likely due to blockade of long-range signal entrainment [65]. Similarly, recent electron microscopy studies in the ovine pituitary have shown that lactotroph-lactotroph junctional contacts increase in line with the circannual peak of PRL during the nonbreeding season [84]. Therefore, episodes of structural and functional plasticity within the lactotroph population/network …”
Section: Lactotrophsmentioning
confidence: 93%
“…In long- and short-day seasonal breeders, we have shown that although the gonadotrope cell population in the pars distalis remains relatively constant throughout the annual reproductive cycle, with little or no change in gonadotrope subtypes, incidence, and intergonadotrope contacts [7], [12], [13], [62], the lactotrope cell population displays increased intercellular contacts and gonadal-independent enhanced cellular prevalence during the long days of summer [7], [13]. The upregulation in lactotrope intercellular communication was shown to be accompanied by changes in cellular ultrastructure, with increased rough endoplasmic reticulum, secretory granule density, and total cell area at this time of year.…”
Section: Intercellular Contacts Underlying Paracrine Regulation Of Pimentioning
confidence: 97%
“…The incidence of gonadotropes is relatively constant throughout the year in the pars distalis [7], [11] and has been shown to be upregulated only in the pars tuberalis of sexually active females [10], [12]; conversely, the lactotrope population, which is only present in the pars distalis, undergoes dynamic changes in response to photoperiod. In sheep, the lactotrope cell area is larger in the nonbreeding season (summer) [13], [14], whereas in the horse, gonadal independent effects of season were reported in orchidectomized animals, with an increase in the incidence of lactotropes in the breeding season (summer) [7]. Moreover, the ultrastructure of lactotrope cells exhibits dynamic changes throughout the year in the ovine pituitary, with hypertrophy, increased cytoplasmic area, and increased rough endoplasmic reticulum and density of prolactin secretory granules during the long days of summer [13].…”
Section: Morphologic Associations Between the Gonadotropic And Lactotmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed increase in the secretion of LH from the pituitary gonadotropic cell in response to the prolonged administration of melatonin results from the increase in the GnRH pulse frequency released by the hypothalamus (Clarke and Arbabi 2016;Ciechanowska et al 2017). The effects of melatonin on the hypothalamic-pituitary axis are related to its diffusion into the cerebrospinal fluid (CSF) in the third ventricle of the brain, which enables the direct effect of melatonin on the secretion of hormones from the pituitary gland (Tricoire et al 2002;Christian et al 2015).…”
mentioning
confidence: 99%